A Review of the Structure and Meaning of the Song Dendang Dikideng by Alfred Gare ft Pax Group - Afrilianus, Mastodius (Universitas Negeri Surabaya, 2025)
Dendang Dikideng is a song originating from the city of Maumere, Sikka district, East Nusa Tenggara. This song was created by Alfred Gare and composed together with the Pax group. The purpose of this research is to find out the song structure in the form of motifs, phrases, and periods, as well as the meaning of this song. This research was conducted using a descriptive qualitative method. The research was conducted at the researcher's house, music reading room, St Gabriel Maumere High School, Sikka Regent Office and Banyu Urip, lor. The subjects in this research are Alfred Gare and the Pax Group. Sources of research data were obtained through informant interviews, observation, and documentation. Data analysis techniques are data reduction, data presentation, and conclusion. The results in this study are the structure of the song Dendang Dikideng, opened with an Intro, verse 1, verse 2, and a reff, after the reff continued with folk song singing and repeated the reff, an interlude, verse 2, a reff, continued with folk song singing, a reff, and closed with an outro. The song Dendang Dikideng is divided into three parts, namely part A, part B, and part C. Each part consists of motifs that then form a motive that is then formed into a song. Each part consists of motifs that then form a phrase and period. This song tells about culture and as a medium of self-identity of the people of East Nusa Tenggara (FLOBAMORA), who, on average, have dark skin